Cash flow management organization as a coordinated social education - Blazhevich, O.; Burkaltseva, D.; Niyazbekova, Sh. (Journal of Economic Research & Business Administration, 2020)
The contribution of domestic and foreign scientists to the solution of cash flow management issues is significant, but one should pay attention to the objective need to further deepen the theoretical framework for determining the nature of cash flows, their classification, as well as the mechanism of an effective cash flow management policy of the organization as a coordinated social education. The aim of this work is to substantiate the theoretical and practical aspects of managing the organization’s cash flows as a coordinated social education. The following tasks were identified: to highlight the theoretical aspects of the essence of the organization’s cash flows; improve the classification of cash flows of the organization; develop a mechanism for managing the organization’s cash flows. The practical significance of the work lies in the fact that its results can be used by organizations to improve the organization’s cash flow management. Research methodology. In the study of the cash flow management process at the enterprise, a number of scientific research methods were used: deduction method, analysis method, synthesis method, comparison method. Based on the analysis of economic literature, the nature of the organization’s cash flows has been clarified, the term “cash flows” has been defined – this is the process of movement of cash and non-cash funds and their equivalents, carried out in the form of revenues from the main and non-core activities of the organization, as a coordinated social education, as well as the payments necessary for the implementation of its economic activities, which, in their totality, are distributed over time and ensure that the organization achieves its main goal is to make a profit, and also support its business activity, a high level of liquidity and solvency, a positive business the image. The classification of cash flows has been clarified and supplemented with the following classification features: according to the degree of dependence on sales volumes, sources of incoming cash flow generation, relative to the number of cash flows, according to the degree of balance, depending on the period of receipt (payment), and priority. The scheme of the organization’s cash flow management mechanism as a coordinated social education has been improved.